Desenvolvimento e caracterização de compósitos poliméricos poliéster/nanocelulose - Lavoratti, Alessandra (My University, 2015)
The search for low-impact, renewable materials is a recent research topic. The need to substitute materials from non-renewable sources is one of the main motivations for such studies in this area. In this context, one of the most promising materials is cellulose, the most abundant biomass on Earth. Cellulose can be obtained from many natural sources, but it is also largely discarded by the paper and wood industry. As such, it is necessary to give these residues a proper destination, and the processing of cellulose waste into nanocellulose is one of the alternatives. The application of nanocellulose in composites is greatly studied, as these materials have many advantages, such as good optical and mechanical properties, weight reduction and recyclability. The present study aims to enable low-cost production of cellulose nanofibers (CNF) from Pinus sp. (CNF-P) and Eucalyptus sp. (CNF-E) cellulose waste, and to evaluate the physical, thermal and dynamic-mechanical properties of polyester resin/nanocellulose composites. Cellulose waste was ground in water (3% wt per volume) in a Masuko MKCA 6-2 grinder at 2,500 rpm until gel was formed. Solvent exchange steps to ethanol 96 °GL were performed, and the gel suspension was dried in a supercritical dryer, using carbon dioxide as supercritical fluid. The obtained nanofibers were dispersed in polyester resin in concentrations of 0.5, 1 and 2 wt%. The samples were prepared by resin casting into rubber silicone molds, and cured in situ at 25 °C for 24 h. Two post-curing steps were performed: 6 h at 80 °C and 2 h at 120 °C. The CNFs were evaluated on their chemical composition and density. Thermogravimetric analysis (TGA), infrared spectroscopy with Fourier transform (FTIR), X-ray diffraction (XRD) and and field emission gun scanning electron microscopy (FEG-SEM) were also performed. Composite samples were evaluated on their density and water absorption. The dynamic mechanical analysis (DMTA) of the composites was performed at different frequencies. Thermal mechanical analysis was used to evaluate the coefficient of thermal expansion of the composites. Low-density (aproximately 0.3 g/cm³) CNFs with a mean diameter of 70-90 nm were succesfully obtained. The chemical composition of the cellulose waste revealed that both have a high initial cellulose content of 72.7 % for unbleached Pinus sp. and 92.6% for bleached Eucalyptus sp. The overall chemical composition of the original cellulose and the obtained CNFs evaluated by FTIR was not changed. CNFs were less thermally stable than the cellulose waste. The crystallinity index of CNFs reduced after grinding. Density of the composites was not altered. Water absorption tests revealed that the CNF-E-1% composite had the lowest values, close to that of the neat resin. The storage modulus obtained by DMTA was the highest for CNF-E-2%. Loss modulus was higher for all composites in comparison with the neat resin, evidencing interactions in the fiber/matrix interface. Glass transition temperature was not significantly altered. The activation energy of the alpha transition was the highest for CNF-E-1%, which may denote better interaction at the fiber/matrix interface. The lowest thermal expansion values were found for CNF-E composites, and the CNF-E-1% composite had a CTE 60% lower than neat resin at 130 °C. Overall, bleached Eucalyptus sp. was found to be a more efficient source of CNFs in this study, yielding the best dynamic mechanical and thermal properties.
A busca por materiais provenientes de matérias-primas renováveis e de baixo impacto ambiental é um dos campos que mais atrai pesquisadores na área da engenharia. A necessidade de substituir materiais oriundos de fontes não sustentáveis, tais como o petróleo, é o principal fator que motiva os estudos nessa área. Um dos materiais mais promissores nesse campo é a celulose, biomassa mais abundante no planeta. A celulose pode ser obtida de fontes naturais, mas também é descartada pelas indústrias moveleira e papeleira. É necessário dar um destino a esse resíduo, e a sua transformação em nanocelulose é uma das alternativas. A aplicação da nanocelulose em compósitos é muito visada, pois estes materiais podem oferecer uma série de vantagens: boas propriedades óticas e mecânicas, estabilidade dimensional e reciclabilidade. Assim, o presente estudo tem como objetivo obter celulose nanofibrilada (CNF) a partir de resíduos de celulose não branqueada de Pinus sp. (CNF-P) e de celulose branqueada de Eucalyptus sp. (CNF-E), e avaliar as propriedades físicas, térmicas e dinâmico-mecânicas dos compósitos CNF/resina poliéster. Os resíduos de celulose foram moídos em moinho Masuko MKCA 6-2 (3% m/v). Foi feita troca de solvente para álcool 96 °GL, e a suspensão foi seca em extrator supercrítico. As CNFs obtidas foram dispersas em resina poliéster utilizando agitação mecânica nas concentrações de 0,5%, 1% e 2%. Os compósitos foram preparados por casting de resina. Foi avaliada a composição química da polpa de celulose, e foi realizada caracterização da celulose de origem e das CNFs obtidas através de espectroscopia no infravermelho com transformada de Fourier, análise termogravimétrica, difração de raios X, microscopia eletrônica de varredura. Os compósitos foram avaliados quanto às suas propriedades físicas, dinâmico-mecânicas e termomecânicas . Foram obtidas nanofibras de celulose com diâmetro médio de 70-90 nm e densidade aproximada de 0,3 g/cm³. A celulose de Pinus sp. e a celulose de Eucalyptus sp. tiveram percentual de α-celulose de 72,7% e 92,6%, respectivamente. A composição química das CNFs não foi alterada durante os processos de micronização e de secagem supercrítica. A cristalinidade das CNFs obtidas diminui após a moagem. A densidade dos compósitos não foi alterada. O compósito CNF-E-1% teve menor absorção de água, próxima aos valores da resina pura. O módulo de armazenamento dos compósitos foi mais elevado para o compósito CNF-E-2%. Na análise do módulo de perda, todos os compósitos dissiparam mais energia em relação à resina pura, evidenciando boa interação na interface fibra/matriz. A temperatura de transição vítrea não foi alterada significativamente. A energia de ativação na transição-alfa aumentou no compósito CNF-E-1%, indicando melhor interação na interface. O menor coeficiente de expansão térmica foi encontrado para o compósito CNF-E-1%, cujo valor foi 60% menor do que o da resina pura na temperatura de 130 °C. De modo geral, as fibras branqueadas de Eucalyptus sp. mostraram ser uma alternativa melhor e mais eficiente para obtenção de CNFs, possibilitando a obtenção de compósitos com melhores propriedades dinâmico e termomecânicas.
Keywords: Nanotecnologia; Nanocompósitos (Materiais); Compósitos poliméricos; Celulose